Predictive levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6), plasma T cells, NK cells as well as B cells in treating diffuse large B-cell lymphoma receiving rituximab: Predictive levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6) - Ye, Jiagui (Journal of Medical Biochemistry, 2025)
Aim: To explore the effect of rituximab in combination with chemotherapy in treating diffuse large B-cell lymphoma,and levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6), plasma T cells, NK cells as well as B cells. Methods: 80 patients admitted to Lujiang County People’s Hospital from January 2022 to January 2024 were included. The control group accepted cyclophosphamide, doxorubicin, vincristine, and prednisone chemotherapy regimen. On the basis of the control group, the research group was treated with rituximab. Serum related factors. 4 mL of fasting venous blood was obtained from patients. After centrifugation, the serum was separated. The levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) along with interleukin-6 (IL-6) were detected by RT-96A enzyme marker (Shenzhen Mindrays Medical Electronics Co., LTD.). The ELISA kit was purchased from Shenzhen Jingmei Biotechnology Co., LTD. Lymphocyte subsets index. Blood samples of the two groups were collected, and the plasma T cells, NK cells as well as B cells of the two groups were detected by flow cytometry. Results: The total clinical effective rate of the research group was better relative to the control group (P<0.05). After therapy, compared to the control group, vascular endothelial growth factor, thymidine kinase 1, and interleukin-6 levels in the research group presented lower (P<0.05), plasma T cells, natural killer cells along with B cells in the research group presented lower (P<0.05), and Quality of Life Core Questionnaire-Core 30 scores in the research group presented higher (P<0.05). No difference was seen in the occurrence of adverse reactions between 2 groups (P>0.05). Conclusion: In conclusion, Rtuximab in combination with chemotherapy patients can promote the therapeutic effect, lessen the level of serum related factors, promote the immune function, as well as promote the quality of life in patients with diffuse large B-cell lymphoma.